Applied Statistics and Probability For Engineers [8th ed.] - Mongtgomery, Douglas C; Douglas C. Montgomery; George C. Runger (Delhi : Wiley, 2007)
This best-selling engineering statistics text provides a practical approach that is more oriented to engineering and the chemical and physical sciences than many similar texts. It's packed with unique problem sets that reflect realistic situations engineers encounter in their working lives. About The Author: Douglas C. Montgomery, Professor of Engineering and Statistics at Arizona State University, received his B.S., M.S., and Ph.D. degrees from Virginia Polytechnic Institute, all in engineering, from 1969 to 1984 he was a faculty member of the School of Industrial & Systems Engineering at the Georgia Institute of Technology; from 1984 to 1988 he was at the University of Washington, where he held the John M. Fluke Distinguished chair of Manufacturing Engineering, was Professor of Mechanical Engineering, and Director of the Program in industrial Engineering. Dr. Montgomery has research and teaching interests in industrial statistics including statistical quality control techniques, design of experiments, regression analysis and empirical model building, and the application of operations research methodology to problems in manufacturing systems. He has authored and coauthored many technical papers in these fields and is an author of twelve other books. Table Of Contents: ?Chapter 1. The Role of Statistics in Engineering. ?Chapter 2. Probability. ?Chapter 3. Discrete Random Variables and Probability Distributions. ?Chapter 4. Continuous Random Variables and Probability Distributions. ?Chapter 5. Joint Probability Distributions. ?Chapter 6. Random Sampling and Data Description. ?Chapter 7. Point Estimation of Parameters. ?Chapter 8. Statistical Intervals for a Single Sample. ?Chapter 9. Tests of Hypotheses for a Single Sample. ?Chapter 10. Statistical Inference for Two Samples. ?Chapter 11. Simple Linear Regression and Correlation. ?Chapter 12. Multiple Linear Regression. ?Chapter 13. Design and Analysis of Single-Factor Experiments: The Analysis of Variance. ?Ch
Keywords: Mathematics